2017
DOI: 10.2147/ijn.s137347
|View full text |Cite
|
Sign up to set email alerts
|

Development and optimization of an injectable formulation of copper diethyldithiocarbamate, an active anticancer agent

Abstract: Copper diethyldithiocarbamate (Cu(DDC) 2 ) is the active anticancer agent generated when disulfiram (DSF) is provided in the presence of copper. To date, research directed toward repurposing DSF as an anticancer drug has focused on administration of DSF and copper in combination, efforts that have proven unsuccessful in clinical trials. This is likely due to the inability to form Cu(DDC) 2 at relevant concentrations in regions of tumor growth. Little effort has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 40 publications
(102 reference statements)
0
40
0
Order By: Relevance
“…Cu(DDC) 2 containing liposomes were prepared by using the method described by Wehbe et al [45,51], which provides the formation of the active Cu In order to prepare hyaluronic acid decorated liposomes, the conjugates HA 4800 -DPPE or HA 17000 -DPPE, in molar ratio of 3 or 5%, were added during the hydration phase of lipid film. In this way, the phospholipidic chain was incorporated into the liposome membrane, while the HA was exposed toward the aqueous phase.…”
Section: Cu(ddc) 2 Containing Liposomesmentioning
confidence: 99%
“…Cu(DDC) 2 containing liposomes were prepared by using the method described by Wehbe et al [45,51], which provides the formation of the active Cu In order to prepare hyaluronic acid decorated liposomes, the conjugates HA 4800 -DPPE or HA 17000 -DPPE, in molar ratio of 3 or 5%, were added during the hydration phase of lipid film. In this way, the phospholipidic chain was incorporated into the liposome membrane, while the HA was exposed toward the aqueous phase.…”
Section: Cu(ddc) 2 Containing Liposomesmentioning
confidence: 99%
“…DDC at millimolar concentrations (0,5-1 мМ) is used as a Cu,Zn-SOD inhibitor, which produces a prooxidant effect; however, under some conditions, it exhibits antioxidant and antiapoptotic properties [11] , [12] . Under in vivo conditions, DDC appears in the bloodstream as a result of the metabolism of the anti-alcohol drug disulfiram (DSF) and undergoes further transformations in the liver and kidneys [13] , [14] , [15] . There is substantial evidence in the literature indicating that, due to the binding of copper ions, DTC produce a pronounced cytotoxic effect [13] , [14] , [16] , [17] , [18] .…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the active metabolite of DSF when it is used in combination with copper is a dithiocarb-copper complex [17] , [34] . Because this complex can damage normal tissues, different ways to increase the DSF toxicity without the use of copper ions and to protect the adjacent tissues by encapsulating the components into micro- and nanoparticles are developed to date [15] , [35] , [36] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, co-administration of DSF and Cu 2+ in two separate formulations usually yielded a very low concentration of the active ingredient, Cu(DDC) 2, in the tumor region and resulted in only marginal anticancer efficacy. Therefore, the delivery of preformed Cu(DDC) 2 in a single formulation is a more effective method to achieve a higher Cu(DDC) 2 concentration in tumor and improve the anticancer efficacy [6].…”
Section: Introductionmentioning
confidence: 99%